Satu Data Indonesia in Sectoral Statistics: Concept of Satu Data Metadata Framework (SDMF) - Hakiki Sandhika Raja; Chaidir Arsyan Adlan (Politeknik Statistika STIS, 2021)
Satu Data Indonesia is a policy contrive to encourage the problem of inadequate data governance in Indonesia. This policy makes 4 main principles, namely metadata, data standards, reference codes, and interoperability as metrics of success in its implementation. In this study, we analyze the satu data Indonesia implementation in Kutai Timur Regency. We found that the integration of the satu data principle is challenging to apply technically because sectoral data in Indonesia has 2 characteristics based on the preparation of the list of data needs, namely the centralized data list, and the decentralized data list. Decentralized data list is a list of data that is partially prepared in each agency without any coordination with other stakeholders for completing the satu data principles. To accommodating this condition, we design the Satu Data Metadata Framework (SDMF) a data standard framework that is in accordance with the conditions of data governance in Indonesia. SDMF utilizes contextual layer and discovery layer of metadata to provide temporal attribute called Satu Data Resource Identifier (SDRI) for integration purpose